2024
DOI: 10.1038/s41467-024-44728-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature grapho-epitaxial La-substituted BiFeO3 on metallic perovskite

Sajid Husain,
Isaac Harris,
Guanhui Gao
et al.

Abstract: Bismuth ferrite has garnered considerable attention as a promising candidate for magnetoelectric spin-orbit coupled logic-in-memory. As model systems, epitaxial BiFeO3 thin films have typically been deposited at relatively high temperatures (650–800 °C), higher than allowed for direct integration with silicon-CMOS platforms. Here, we circumvent this problem by growing lanthanum-substituted BiFeO3 at 450 °C (which is reasonably compatible with silicon-CMOS integration) on epitaxial BaPb0.75Bi0.25O3 electrodes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…On the other hand, the use of solvent-free chemical deposition techniques such as atomic layer deposition could be an attractive route toward all-chemical complex oxide membranes. Finally, further investigations on the interplay between strain gradient, phase distortion, and superflexibility in these complex oxides could offer many practical applications in sensors, memories, spintronics, electronic skins, and self-powered devices. , These broad range of possibilities could also be extended to other piezoelectric, ferroelectric, and multiferroic perovskite oxides anticipating a rich playground for complex oxide freestanding membranes to create new functional materials.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the use of solvent-free chemical deposition techniques such as atomic layer deposition could be an attractive route toward all-chemical complex oxide membranes. Finally, further investigations on the interplay between strain gradient, phase distortion, and superflexibility in these complex oxides could offer many practical applications in sensors, memories, spintronics, electronic skins, and self-powered devices. , These broad range of possibilities could also be extended to other piezoelectric, ferroelectric, and multiferroic perovskite oxides anticipating a rich playground for complex oxide freestanding membranes to create new functional materials.…”
Section: Resultsmentioning
confidence: 99%
“…This represents the most common approach used for altering the strain at the interface between the epitaxial film and the substrate and the resulting magnetic and electric properties [ 27 , 28 ]. Interfacial effects such as epitaxial strain [ 29 ], interface quality (i.e., defect, roughness, sharpness) [ 30 , 31 , 32 ], interdiffusion, and chemical intermixing [ 33 , 34 ] in multiferroic heterostructures have attracted tremendous attention for tuning and understanding the structure–property relationships as they allow one to control the magnetic interaction [ 35 ], spin ordering [ 36 , 37 ], and coupling across heterointerfaces, including ferromagnetic (FM)/antiferromagnetic (AFM) bilayer systems [ 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Several studies reported the occurrence of an exchange interaction based on the exchange bias (EB) at the interface of FM/AFM heterostructures.…”
Section: Introductionmentioning
confidence: 99%